PENGARUH PENGALAMAN AUDITOR, PROFESIONALISME, DAN INDEPENDENSI TERHADAP KETEPATAN PEMBERIAN OPINI AUDIT DENGAN AUDIT JUDGEMENT SEBAGAI VARIABEL MODERATING - Kiki Putri Dwi Novianti (Behavioral Accounting Journal, 2019)
This study aims to analyze the effect of auditor experience, professionalism and independence influencing audit assessment, which also aims to analyze audit assessments to strengthen auditor experience, professionalism, and independence of the accuracy of audit results. This type of research is quantitative research. The sample in this study was 75 respondents who were calculated using the Slovin formula. The data source of this research is an auditor who works in a public accounting firm in Surabaya. Data collection techniques using a questionnaire taken by drawing. Test the hypothesis by comparing the results of the path coefficient with the T-table with the Partial Least Square (PLS) approach. The results showed that the influence of auditor experience, professionalism, and independence influences the accuracy of opinion results. Audit judgment strengthens experience and independence influences the accuracy of opinion results, while audit judgment does not affect the strengthening of professionalism regarding the accuracy in providing audit opinion.